Effects of vitamin D supplementation on muscle strength in middle-aged and elderly individuals: a retrospective, propensity score-matched study - Qi, Peiyao; Fu, Xiaomin; Zhao, Dan; Li, Chunlin; Lu, Yanhui; Li, Nan (Frontiers in Nutrition, 2024)
In middle-aged and elderly populations, vitamin D deficiency can contribute to impaired bone mineralization and osteoporosis, significantly elevating the risk of fractures and falls. Increased muscle strength is regarded as a key factor in the prevention of falls and fractures, and improving the status of vitamin D may represent a straightforward approach to achieving these critical objectives. The current evidence does not support the beneficial effects of vitamin D supplementation on muscle health and may even suggest potential adverse effects. Further clinical data are still required to establish the correlation between vitamin D supplementation and muscle strength conclusively. This study explored the effects of vitamin D supplementation on muscle strength in middle-aged and older adults through the propensity score matching method. Our findings suggest that vitamin D supplementation combined with lifestyle counseling and health education was beneficial in increasing upper and lower limb strength.